2009
DOI: 10.1016/j.ccr.2009.01.002
|View full text |Cite
|
Sign up to set email alerts
|

gp130-Mediated Stat3 Activation in Enterocytes Regulates Cell Survival and Cell-Cycle Progression during Colitis-Associated Tumorigenesis

Abstract: Although gastrointestinal cancers are frequently associated with chronic inflammation, the underlying molecular links have not been comprehensively deciphered. Using loss- and gain-of-function mice in a colitis-associated cancer model, we establish here a link comprising the gp130/Stat3 transcription factor signaling axis. Mutagen-induced tumor growth and multiplicity are reduced following intestinal epithelial cell (IEC)-specific Stat3 ablation, while its hyperactivation promotes tumor incidence and growth. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
768
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 858 publications
(819 citation statements)
references
References 52 publications
46
768
1
4
Order By: Relevance
“…Gp130 is a glycoprotein that mediates the activation of key pro-survival pathways crucial for tumor cell proliferation, invasion and angiogenesis. 21,33,34 Amplification of gp130 gene and the abnormal stabilization of the gp130 protein have been shown to be closely associated with tumor progression. 33,34 The protein level of gp130 in normal cells is tightly regulated at the post-translational level by the ubiquitindependent degradation, endocytosis and caspase-induced proteolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gp130 is a glycoprotein that mediates the activation of key pro-survival pathways crucial for tumor cell proliferation, invasion and angiogenesis. 21,33,34 Amplification of gp130 gene and the abnormal stabilization of the gp130 protein have been shown to be closely associated with tumor progression. 33,34 The protein level of gp130 in normal cells is tightly regulated at the post-translational level by the ubiquitindependent degradation, endocytosis and caspase-induced proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…21,33,34 Amplification of gp130 gene and the abnormal stabilization of the gp130 protein have been shown to be closely associated with tumor progression. 33,34 The protein level of gp130 in normal cells is tightly regulated at the post-translational level by the ubiquitindependent degradation, endocytosis and caspase-induced proteolysis. 29,35,36 It is highly possible that the abnormally elevated gp130 protein level in tumor cells may be caused by dysregulated post-translational processes.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 induction by ras gene is a crucial factor for tumor growth in DMBA-TPA-induced skin carcinogenesis model (Ancrile et al, 2007). It also promotes proliferation and survival of pre-malignant intestinal epithelial cells and subsequently enhances the initiation and progression of colitisassociated cancer (Bollrath et al, 2009;Grivennikov et al, 2009). Drachenberg et al (1999) suggested that serum IL-6 level can be used as a maker in patients with cancer metastatic state (Drachenberg et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…After dry, slides were photographed in a microscope attached with camera at different magnifications Karin and Greten, 2005;Pikarsky et al, 2004;Baud and Karin, 2009). Given their central roles in inflammation and cancer (Karin and Greten, 2005;Baud and Karin, 2009;Yu and Jove, 2004;Yu et al, 2007;Zhong et al, 1997;Bromberg et al, 1999) among other signaling STATs, particularly STAT3, is highly interconnected with NF-κB signaling (Lu and Stark, 2004;Bollrath et al, 2009;Grivennikov et al, 2009;Lee et al, 2009). There are striking parallels, as well as contrasts, between NF-κB and STAT3.…”
Section: Nuclear Factor -κBmentioning
confidence: 99%